2011
DOI: 10.1080/1745039x.2011.588849
|View full text |Cite
|
Sign up to set email alerts
|

Determination of energy and amino acid digestibility in growing pigs fed corn distillers' dried grains with solubles containing different lipid levels

Abstract: Two experiments were conducted to estimate the digestibility of energy, nitrogen and amino acids (AA) in growing pigs fed diets containing one of five corn distillers' dried grains with solubles (DDGS), including three normal oil DDGS (NO-DDGS) and two low oil DDGS (LO-DDGS) samples. Exp. 1 was conducted to determine the digestible energy (DE) and metabolisable energy (ME) content. Six growing barrows (initial body weight [BW]: 35.1 +/- 2.2 kg) were allotted to a 6 x 6 Latin square design, with six periods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
1
27
3
Order By: Relevance
“…a-c Means within a row without a common superscript letter are significantly different (P<0.05). for DE; 10.30 and 11.55 MJ/kg DM for ME, respectively) were higher than the values published by the National Research Council (2012), may be because of the higher content of EE (Ren et al, 2011). It has been reported that the presence of fibre could increase the endogenous secretions of CP and that fat associated with the increasing microbial mass could lead to a decrease in digestion of CP and fat (Sauer and Ozimek, 1986;Noblet and Perez, 1993).…”
Section: Resultscontrasting
confidence: 46%
“…a-c Means within a row without a common superscript letter are significantly different (P<0.05). for DE; 10.30 and 11.55 MJ/kg DM for ME, respectively) were higher than the values published by the National Research Council (2012), may be because of the higher content of EE (Ren et al, 2011). It has been reported that the presence of fibre could increase the endogenous secretions of CP and that fat associated with the increasing microbial mass could lead to a decrease in digestion of CP and fat (Sauer and Ozimek, 1986;Noblet and Perez, 1993).…”
Section: Resultscontrasting
confidence: 46%
“…Generally, DE and ME values of RO-cDDGS were lower than those published for conventional corn DDGS (Stein and Shurson 2009). Our calculated DE and ME values for RO-cDDGS were similar to values given by Ren et al (2011), were higher than values reported by Jacela et al (2011) and Dahlen et al (2011), and were lower than values cited by Kerr et al (2013) and Anderson et al (2012). These researchers fed solvent-extracted corn DDGS with 3.15% crude fat versus 6.7% crude fat in the RO-cDDGS fed in the current trial.…”
Section: Discussion Energy Value Of Reduced-oil Vs Conventional Corncontrasting
confidence: 49%
“…The majority of US ethanol plants are currently extracting oil from DDGS (Jessen 2013) thereby reducing its dietary energy value. Five studies have been published that determined the DE and ME values of RO-cDDGS (Dahlen et al 2011;Ren et al 2011;Jacela et al 2011;Anderson et al 2012;Kerr et al 2013). Generally, DE and ME values of RO-cDDGS were lower than those published for conventional corn DDGS (Stein and Shurson 2009).…”
Section: Discussion Energy Value Of Reduced-oil Vs Conventional Cornmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have evaluated the DE and metabolisable energy (ME) content of corn DDGS (Pedersen et al 2007;Mendoza & Ellis 2010;Ren et al 2011;Anderson et al 2012;Kerr et al 2013), but the number of samples (especially for the de-oiled DDGS) was usually limited. Li et al (2015) determined the ME content of 25 DDGS samples; 10 of them were de-oiled.…”
Section: Introductionmentioning
confidence: 99%